2019
DOI: 10.5194/cp-2019-64
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Droughts in the area of Poland in recent centuries

Abstract: Abstract. The paper presents the main features of droughts in Poland in recent centuries, including their frequency of occurrence, coverage, duration and intensity. For this purpose both proxy data (documentary and dendrochronological) and instrumental measurements of precipitation were used. The reconstructions of droughts based on all the mentioned sources of data covered the period 996–2015. Examples of megadroughts were also chosen using documentary evidence, and some of them were described. Various docume… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…In addition, Zhang et al [33], using the self-calibrating Palmer Drought Severity Index, confirmed our findings, and concluded that the sensitivity of precipitation was higher than that of ET o . Our finding, the high contribution rate of P, would also be a potential evidence and explanation as to why the P-based indices like the SPI show a high level of consistency with the SPEI, and a considerable adaptability in most times and places, such as the findings of Yao et al [34], Wang et al [57], Chen et al [8], and Przybylak et al [30].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In addition, Zhang et al [33], using the self-calibrating Palmer Drought Severity Index, confirmed our findings, and concluded that the sensitivity of precipitation was higher than that of ET o . Our finding, the high contribution rate of P, would also be a potential evidence and explanation as to why the P-based indices like the SPI show a high level of consistency with the SPEI, and a considerable adaptability in most times and places, such as the findings of Yao et al [34], Wang et al [57], Chen et al [8], and Przybylak et al [30].…”
Section: Discussionsupporting
confidence: 62%
“…The SPEI at the 1 to 6 month time scale is most appropriate to monitor drought impacts with regard to meteorological and agroecological systems, while the SPEI at the 7 to 18 month time scale is appropriate for the drought identification for hydrological systems [8,9,63]. Some other authors also report that 1, 3, and 24 month time scales are used as a good proxy for meteorological, agricultural, and hydrological [30].…”
Section: Spei Sensitivity Analysis At Different Time Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase in human population on Earth (with accompanying increase in water demand), increasing intensification of agriculture [7,8], as well as disturbing climatic changes observed in recent years, i.e. global warming and drought [9], significantly inhibit rational management of available resources of water in Poland, which status, due to multiple indicators (e.g. oxygen, fluorides, biogenic substances) being exceeded, is considered as bad [10].…”
Section: Introductionmentioning
confidence: 99%